SISTEM INFORMASI MANAGEMENT PERCETAKAN ONLINE AZAGI PRINT BERBASIS WEB - Yogi Afandi; Endar Nirmala (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
In the era of the development of information technology that is increasingly sophisticated today there are still printing service companies doing marketing still using print media such as banners, banners, leaflets meanwhile, to order customer products, you must come directly to the location of the printing service. Over time product marketing using banners, banners, leaflets and product orders requires customers to come directly is considered less effective so that it has an impact on the lack of information obtained by customers. For this reason, a media in the form of a website is needed as a marketing and sales system for printing services to be able to improve services and data processing more effectively and efficiently. The research method used is a data collection technique consisting of observation, interviews, literature studies, while the system development model used is a waterfall model consisting of four stages, namely the analysis stage, the design stage, the testing stage and the implementation stage. As a result, the Web-Based Azagi Print Online Printing Management Information System can be used as a source of product and marketing information for printing service companies and can expand the marketing reach, as well as facilitate companies in the process of data processing, data search and making printing order data reports.